Millie and the Lords - Carmona, Jennica; Carmona, Jessica; Gómez, Mateo; Huereca, Alfredo (Si Se Puede Productions, LLC, 2015)
Millie and the Lords tells the story of Milagros Baez, a young, working class under-confident Puerto Rican woman whose life is changed for the better when she begins to learn about the Young Lords Party and her rich Puerto Rican history.--